A Narrative Review on the Prevalence of Plasmodium falciparum Resistance Mutations to Antimalarial Drugs in Rwanda - Muharib Alruwaili; Abozer Elderdery; Emad Manni; Jeremy Mills (Tropical Medicine and Infectious Disease)
Malaria has been and remains a significant challenge in Africa and other endemic settings. Roughly, 95% of global morbidity and mortality due to malaria occurs within African populations and affects millions of individuals, especially those living in sub-Saharan countries, predominantly due to disease complications. Cultural factors such as unawareness of and disinterest in using recommended preventive tools and combating the primary host (i.e., the female Anopheles mosquito) play a significant role. This host transmits the malaria-causing Plasmodium parasite by biting an infected individual and spreading it to humans. The current overview focuses on the molecular markers associated with antimalarial drug resistance in Plasmodium falciparum (P. falciparum) in Rwanda, considered an exemplar of sub-Saharan countries where malaria is prevalent and effective policies on the development of malaria treatment, approved recently by WHO in 2025, have been adopted. The prevalence of mutations in key resistance genes, including pfcrt, pfmdr1, and pfdhfr/pfdhps, are linked to resistance against common antimalarial drugs such as chloroquine and sulfadoxine-pyrimethamine (SP). In addition, the Plasmodium falciparum kelch13 (pfk13) gene is linked to resistance against artemisinin, as its mutations can cause delayed parasite clearance and treatment failure. Despite changes in therapeutic use policies owing to high prevalence of variant alleles, which reduce the drug’s efficacy resistance to SP, the gene persists in Rwanda. Malaria parasites are becoming more resistant to chloroquine, leading to diminished effectiveness and slower recovery or treatment failure. Surveillance data reported from several studies provide crucial insights into the evolving trends of resistance markers and are vital for guiding treatment protocols and informing therapeutic use policy decisions. It is important that we continue to maintain and develop the effectiveness of malaria prevention strategies and treatments, due to the multiple types of resistance found in the population.